2012
DOI: 10.1097/brs.0b013e31824da3ba
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Axial Load on the Flexural Properties of an Elastomeric Total Disc Replacement

Abstract: Effect of axial load on the flexural properties of an elastomeric total disc replacement. Spine 37: E908-E912.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…However, as with the moisture condition, the temperature of spinal devices, such as UHMWPE bearings, or elastomeric devices, may behave in an altogether different manner at room temperature than at body temperature. The testing frequency and preload magnitude has also been shown to affect the sagittal bending properties of the elastomeric Cadisc TDR, 96 highlighting the notion that replicating the in-vivo environment is critical to understanding not only the properties of the natural spine, but also its properties with spinal instrumentation, and ultimately, the effects of the instrumentation.…”
Section: 75mentioning
confidence: 99%
“…However, as with the moisture condition, the temperature of spinal devices, such as UHMWPE bearings, or elastomeric devices, may behave in an altogether different manner at room temperature than at body temperature. The testing frequency and preload magnitude has also been shown to affect the sagittal bending properties of the elastomeric Cadisc TDR, 96 highlighting the notion that replicating the in-vivo environment is critical to understanding not only the properties of the natural spine, but also its properties with spinal instrumentation, and ultimately, the effects of the instrumentation.…”
Section: 75mentioning
confidence: 99%
“…5,23 The simulator has six degrees of freedom: four active (flexion/extension, lateral bend, axial rotation and axial The two generic total disc replacement devices (one with a ball radius of 10 mm and the other with a ball radius of 16 mm) were tested with two different lubricants:…”
Section: Frictional Torquementioning
confidence: 99%
“…More recently, TDR prostheses have been manufactured from flexible polymeric materials to mimic more closely the natural disc. Laboratory studies have shown that the flexibility of a polymeric prosthesis can be comparable to that of a normal human disc 44 with one version predicted to have a fatigue life of about 50 years. 45 It should be noted, however, that such studies cannot reproduce in vivo conditions, and the fixation of a GAGs Active MMPs 6.7 6.5 6.3 Graph showing how a lowered pH level reduces the glycosaminoglycan (GAG) synthesis by disc cells much more than that of matrix metalloproteinase (MMP) production so favouring degradation of the matrix (modified with permission from Razaq MS.…”
Section: Pathology Of Disc Degenerationmentioning
confidence: 99%